Reference percentiles of FEV1 for the Canadian cystic fibrosis population: comparisons across time and countries. Issue 5 (6th February 2018) - Kim, Sang-Ook; Corey, Mary; Stephenson, Anne L; Strug, Lisa J
Abstract : Background: Forced expiratory volume in 1 s (FEV1) indicates lung health in cystic fibrosis (CF). FEV1 is commonly communicated as a per cent predicted of a healthy individual sharing the same age, sex, race and height. CF-specific reference equations are complementary and calibrate a patient's FEV1 to that of their CF peers. Objectives: (1) To derive Canadian CF-specific FEV1 reference percentiles (FEV1%iles), (2) characterize how they have changed over time and (3) compare the Canadian FEV1%iles to those for USA and European CF populations. Method: CF FEV1%iles are calculated using the Canadian CF Registry and quantile regression. Results: The Canadian FEV1%iles demonstrated better lung function in more recent time periods within Canada, especially below the 50% percentile and in males. When compared to USA and European FEV1%iles for the same time period, Canadian FEV1%iles were higher. Conclusion: CF-specific FEV1%iles can provide useful information about changes in lung health. An online calculator (available at cfpercentile.research.sickkids.ca ) makes these FEV1%iles accessible.